A study on future development of China's textile industry - analysis from structure adjustment of industrial textile produces of Huayuan - Li, Yong (2008)
Lists out the measures for structure adjustment through the successful case of China's Huayuan Company’s structure adjustment of industry-use textile. The only way out for the industry, which is under such a fierce competition market, is to actively push the industry structural adjustment and expedite the upgrading.